Technology evaluation and licensing : a literature review and an assessment of the Portuguese universities technology transfer practices - Rocha, António Miguel Sousa (2011)
To improve the access to information about practices supporting the application of research results we looked at strategies and methods described on the literature review and in use by technology transfer units (TTUs) having in mind a set of questions underlying the processes of technology evaluation and licensing in universities. The research questions gave us the opportunity to understand the TTUs degree of selectivity in the protection of inventions, the factors at the origin of licensing agreements and its main obstacles, the main evaluation methods and payment modes and they also gave us the opportunity to know the universities at study structure of dividend distribution. Underneath the answer to this questions we affirmed that the development of complete and demonstrable turnkey solutions and products decreases the investment risk and makes the technology more attractive to potential licensees, and we concluded that only knowing the economic value of an invention can we fully exploit its full potential and can we carry out an appropriate technology valorization strategy.